Population Dynamics of the Exotic Flatworm Obama nungara in an Invaded Garden - Shanèze Noël; Yoan Fourcade; Virginie Roy; Georges Bonnet; Lise Dupont (Ecology and Evolution)
ABSTRACT Population dynamics and the way abundance fluctuates over time may be key determinants of the invasion success of an introduced species. Fine‐scale temporal monitoring of invasive species is rarely carried out due to the difficulties in collecting data regularly and over a long period. Thanks to the collaboration of an amateur naturalist, a unique dataset on the abundance of the invasive land flatworm Obama nungara was obtained during a 4‐year survey of a French private garden, where up to 1585 O. nungara were recorded in 1 month. Daily monitoring data revealed high population size fluctuations that may be explained by meteorological factors as well as intra‐ and inter‐specific interactions. Bayesian modeling confirmed that O. nungara's abundance fluctuates depending on temperature, humidity, and precipitation. Population growth seems to be favored by mild winters and precipitation while it is disadvantaged by drought. These exogenous factors affect both directly this species, which is sensitive to desiccation, and indirectly since they are known to affect the populations of its prey (earthworms and terrestrial gastropods). We also suggested the important resilience of O. nungara population in this site, which was able to recover from a drastic demographic bottleneck due to a severe drought, as well to systematic removal by the owner of the site. These findings highlight the potentially high invasiveness of O. nungara and raise concerns about the major threat these invasive flatworms pose to the populations of their prey.